Corpo, espaço, cidade: tramas de controle e disciplina - os vendedores do comércio ambulante do centro de São Paulo - Julião, Fábio Costa (2012)
The aim of this study is to feature an anthropological and ethnographic reflection of the street vendors, camelôs , marreteiros and ambulantes in the urban space in the central area of São Paulo. The research is based on the interventions on these social actors and their urban territories in a plot where body, space and the city itself are dealt as a related tripod which demonstrates conflicts over the use of the central urban spaces by these and other social and urban actors. Such conflicts reveal the symbolic aspects involving the specific use of these social urban actors and the production of imaginings on the urban center and the popular group activities in this space, which help us to understand some social representations about the central area of São Paulo. Under the circumstances, the central area turns out to be a taboo and a stigmatized space where there are urban alterities that make such places avoidable and considered deteriorated and degraded. However, they should be controlled and disciplined through institutional actions and its knowledge-power in strain with popular uses, signaling symbolic conflicts about the urban space mainly in downtown. We have a vision of the street workers, the ambulant commerce and the relation with a wider society that partly sees its stubborn and obstinate presence in this urban space through the presence of remarkable measures of real control, cleanliness and multiple disciplines present in the inspection about the activity, the popular and well known rapa . Moreover, the media construction of its uses on this same space reinforces the segregation and violence of which they are the target through deliberate actions by the public power, which result in removal and control by the police intervention seen recently